SUCCESSFUL INTELLIGENCE AND METACOGNITIVE THINKING: THE MEDIATING EFFECTS OF SUSTAINABLE EDUCATIONAL DEVELOPMENT AMONG UNIVERSITY STUDENTS (Lex localis - Journal of Local Self-Government, 2025)
This study investigates the direct effects of successful intelligence on metacognitive thinking and SED, the direct impact of SED on metacognitive thinking, and the indirect role of SED as a mediator between successful intelligence and metacognitive thinking. A quantitative analytical cross-sectional design was employed. A stratified-proportionate sample of 529 university students was selected. Standardized scales measuring successful intelligence, metacognitive thinking, and sustainable educational development were adapted and validated. Multiple regression analysis and structural equation modeling (SEM) were used to examine relationships among variables. The findings reveal that successful intelligence has a significant direct positive impact on both metacognitive thinking (β = 0.505, p < 0.05) and SED (β = 0.347, p < 0.05). Additionally, SED significantly enhances metacognitive thinking (β = 0.461, p < 0.05). The results confirm that SED partially mediates the relationship between successful intelligence and metacognitive thinking but indirectly. However, creative abilities had no significant effect on SED, and the economic dimension of SED showed a weaker impact on metacognitive thinking. This study underscores the crucial role of successful intelligence and sustainable educational development in fostering metacognitive thinking among university students. Universities should integrate successful intelligence strategies into curricula, develop metacognitive skill-building programs, and promote sustainability-focused education.